International and European Standards on Prohibition of Racial Discrimination and Law and Practice in Turkey - Aydin,Zeliha (2009)
The purpose of this paper is to provide a brief discussion of recent developments regarding prohibition of discrimination under the International and European human rights and Turkish legal system. Principle of equality and the right to non-discrimination is among the fundamental human rights. Discrimination is a violation of human rights and fundamental freedoms. Various forms of discrimination are found, based on gender, race, ethnicity, sexual orientation, age, disability and so on. Discrimination has found its place in the history of the world and has caused the most serious destruction. It is obvious that discrimination is not exceptionally happens but it is more common case that occurs in every society in the world. Lessons from history make it clear that the fight against discrimination has a significant importance within Europe. Therefore, the Council of Europe has been established in order to promote and protect human rights and fundamental freedoms. Turkey has a rich cultural, ethnic and religious diversity. Turkey's candidacy to the European Union (EU) has led a great reform process on human rights and democratization. Contrary to the reform process, prohibition of discrimination is not priority and much remains to be done for the fulfillment of the prohibition of discrimination in Turkey regarding International and European standards.Even though, the focus of this thesis will be on the non discrimination provisions of the Council of Europe's human rights instrument, Article 14 of the European Convention of Human rights, non discrimination provisions of the core International Human Rights Instruments will be explored. Regarding human rights instruments of the Council of Europe, this thesis will cover the European Convention on Human Rights and its additional Protocols No.12, the case law of the European Court of Human Rights, the Recommendations of the European Commission against Racism and Intolerance (ECRI), the Framework Convention for the Protection of National Minorities, and finally the European Social Charter. Under the Turkish legal system, non discrimination provisions of the Turkish Constitution, Turkish Penal Code, Labour Law, and Civil and Administrative Law will be evaluated. Furthermore as a candidate state to the European Union, the thesis will give a brief explanation on the scope of the EU anti- Discrimination Law and its possible effects on the Turkish legal system. And as a conclusion, the thesis will recommend possible measures for the fulfillment of the prohibition of discrimination in Turkey.
Keywords: International Human Rights Law